Depression and Anxiety in Adult Persons With Epilepsy and Their Caregivers: A Survey-Based Study at a Tertiary Care Center. Issue 3 (March 2022) - Tsamakis, Konstantinos; Teagarden, Diane L.; Villarreal, Hannah K.; Morton, Matthew L.; Janocko, Nicholas J.; Groover, Olivia; Loring, David W.; Drane, Daniel L.; Karakis, Ioannis
Abstract : Abstract: This study evaluated the rates of depression and anxiety and their determinants in adult persons with epilepsy and their caregivers. Both completed surveys about demographic, disease-related, and psychosocial characteristics. One hundred patients and caregivers participated. A mood disorder was present in 89% of patients and 56% of caregivers. In the univariate analysis, the presence of mood disorder in the patient was associated with being unmarried, unemployed, frequent hospitalizations, side effects from polypharmacy, patient stigma, patient quality of life, caregiver anxiety, and caregiver burden. In the multivariate analysis, medication side effects sustained as an important determinant. In the univariate analysis, the presence of mood disorder in the caregiver was associated with seizure frequency, patient anxiety, patient quality of life, caregiver stigma, and caregiver burden. In the multivariate analysis, patient anxiety level and caregiver burden sustained as important determinants. Adult persons with epilepsy and their caregivers experience high rates of mood disorders, explained by certain clinical factors.